Collaborative Leadership of Wali Nagari in Mitigation of the Covid-19 Pandemic in Nagari Rancak - Rizaldi, Syamsu; Ariany, Ria; Putri, Annisa Aulia (Universitas Muhammadiyah Yogyakarta, 2021)
The COVID-19 Pandemic has struck many countries, including Indonesia. The Indonesian government has created and implemented various policies in dealing with this epidemic, from the central government to the villages. The COVID-19 pandemic response at the local level is regulated in a Village Minister Circular Number 8 of 2020. In tackling the outbreak at the village level, leadership that can embrace all stakeholders is required. This study examines further the collaborative leadership of Wali Nagari in mitigating the COVID-19 pandemic in Nagari Rancak in West Sumatra Province. The research approach used was qualitative with descriptive analysis. The research was conducted in five villages in West Sumatra Province. Data collection techniques in the form of interviews and documentation. This study concluded that the three Nagari Rancak, namely Nagari Batu Bulek, Nagari Sungayang, and Nagari Pakan Sinayan, did not apply collaborative leadership to the maximum, while the other two Nagaris, namely the Nyalo IV Koto Mudiek River Village and the Taram Nagari, had implemented a collaborative leadership model. With collaborative leadership, the Nagari’s Wali (leaders) could cover the limitations to overcome COVID-19 impacts in the village.